Hereditary spastic paraplegia: Clinicogenetic lessons from 608 patients. Issue 4 (11th March 2016) - Schüle, Rebecca; Wiethoff, Sarah; Martus, Peter; Karle, Kathrin N.; Otto, Susanne; Klebe, Stephan; Klimpe, Sven; Gallenmüller, Constanze; Kurzwelly, Delia; Henkel, Dorothea; Rimmele, Florian; Stolze, Henning; et al.
Abstract : Objective: Hereditary spastic paraplegias (HSPs) are genetically driven disorders with the hallmark of progressive spastic gait disturbance. To investigate the phenotypic spectrum, prognostic factors, and genotype‐specific differences, we analyzed baseline data from a continuous, prospective cohort. Methods: We recruited 608 HSP cases from 519 families of mostly German origin. Clinical severity was assessed by the Spastic Paraplegia Rating Scale. Complicating symptoms were recorded by a standardized inventory. Results: Family history indicated dominant (43%), recessive (10%), and simplex (47%) disease. We observed a significant male predominance, particularly in simplex cases without a genetic diagnosis. Disease severity increased with disease duration. Earlier disease onset was associated with less severe disease. Specific complicating features including cognitive impairment, extrapyramidal or peripheral motor involvement, and ataxia were associated with worse disease severity. Disease severity also depended on the genotype. HSP cases maintained the ability to walk independently for a median disease duration of 22 years. Early onset cases were able to maintain free walking significantly longer and were at less risk to become wheelchair dependent. Interpretation: This cross‐sectional cohort study provides the first large‐scale data on disease manifestation, progression, and modifying factors, with relevance for counseling of HSP families and planning of future cross‐sectional and natural history studies. Later age of onset, specific complicating features, and the SPG11 genotype are strongly associated with more severe disease. Future interventional studies will require stratification for modifiers of disease progression identified in this study. Prospective longitudinal studies will verify progression rates calculated in this baseline analysis. Ann Neurol 2016;79:646–658